2013
DOI: 10.1111/psyg.12032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of late‐onset schizophrenia in Japan: comparison with early‐onset cases

Abstract: Background: Although the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders abandoned the use of the specifier 'late-onset', a considerable number of studies have reported clinical characteristics of late-onset schizophrenia. Still, only limited research has been conducted on late-onset schizophrenia, especially in Asian countries. In this epidemiological study, the clinical characteristics of late-onset schizophrenia were examined in comparison with early-onset schizophrenia. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
4
3
2
Order By: Relevance
“…Age differences between LOS patients compared to NLOS patients in prior research could have contributed to this discrepancy, as all prior studies included significantly younger patients in the NLOS group, contrary to our study. In fact, the mean age of the NLOS group was consistently in the twenties in previous research 16,22,48 . One exception was Vahia et al.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Age differences between LOS patients compared to NLOS patients in prior research could have contributed to this discrepancy, as all prior studies included significantly younger patients in the NLOS group, contrary to our study. In fact, the mean age of the NLOS group was consistently in the twenties in previous research 16,22,48 . One exception was Vahia et al.…”
Section: Discussionmentioning
confidence: 72%
“…LOS remains largely understudied 1 . In addition, prior research has often been limited by methodological constraints such as reliance on samples including a limited number of subjects from one center, 8,21–23 or important differences in mean age between groups of comparison. This last point is critical because schizophrenia interacts with the aging of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Our results might differ, because we analysed not depressive disorder, but depression dimension in a schizophrenia. Recent study by Yasuda group proved late onset of SCH is characterised by more depressive symptoms [ 33 ]. Study by Emsley showed PANSS scores for depression and anxiety symptoms are more severe in females, first-episode individuals and ones with positive symptoms predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs études se sont penchées sur les caractéris tiques cliniques de la schizophrénie à début tardif en comparaison à la schizophrénie à début précoce [5,[9][10][11][12][13][14][15][16]. Environ 80% des patients schizophrènes âgés vivent dans la communauté.…”
Section: Données éPidémiologiquesunclassified
“…Concernant la survenue d'une schizophrénie à début tardif ou très tardif, la présence d'antécédents de dépression, des traits de personnalité schizoïde et paranoïde prémorbide ainsi que l'isolement social seraient des facteurs de risque potentiels [10,[13][14][15]. Malgré l'importance et l'impact sociétal, il est parlant de mentionner que seulement 1% des études sur la schizophrénie est consacré à la schizophrénie d'appa rition tardive [16].…”
Section: Données éPidémiologiquesunclassified